2009
DOI: 10.1007/s00540-009-0829-1
|View full text |Cite
|
Sign up to set email alerts
|

The intravenous anesthetic propofol inhibits lipopolysaccharide-induced hypoxia-inducible factor 1 activation and suppresses the glucose metabolism in macrophages

Abstract: Our experimental results indicate that propofol inhibits HIF-1 activation and downstream gene expression induced by LPS and suppressed HIF-1-dependent glucose metabolic reprogramming. HIF-1 suppression by propofol in macrophages may explain molecular mechanisms behind the inhibitory effect of propofol on cellular inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 31 publications
(46 reference statements)
2
40
0
Order By: Relevance
“…The authors also demonstrated that propofol does not suppress HIF‐1α mRNA expression; rather, it selectively suppresses the translation of mRNA into protein. A more recent study reported that propofol also inhibits HIF‐1 activation by lipopolysaccharide in macrophages with a resultant reduction in glycolysis‐dependent metabolism 98. This study also concluded that the most likely mechanism behind propofol's inhibitory effect on HIF‐1 was via impaired translation of mRNA.…”
Section: Anesthetics and Direct Effects On Cancer Cell Biologymentioning
confidence: 69%
See 1 more Smart Citation
“…The authors also demonstrated that propofol does not suppress HIF‐1α mRNA expression; rather, it selectively suppresses the translation of mRNA into protein. A more recent study reported that propofol also inhibits HIF‐1 activation by lipopolysaccharide in macrophages with a resultant reduction in glycolysis‐dependent metabolism 98. This study also concluded that the most likely mechanism behind propofol's inhibitory effect on HIF‐1 was via impaired translation of mRNA.…”
Section: Anesthetics and Direct Effects On Cancer Cell Biologymentioning
confidence: 69%
“…A more recent study reported that propofol also inhibits HIF-1 activation by lipopolysaccharide in macrophages with a resultant reduction in glycolysis-dependent metabolism. 98 This study also concluded that the most likely mechanism behind propofol's inhibitory effect on HIF-1 was via impaired translation of mRNA. Interestingly, there is already evidence that clinical concentrations of propofol produce anticancer effects by modulating the GTPase RhoA, thereby inhibiting cancer cells' capacity for migration and invasion.…”
Section: Anesthetics That Downregulate Hifsmentioning
confidence: 82%
“…Antagonism of HIF1A and ADORA2B in BMDMs led to decreases in profibrotic mediator production, suggesting new potential targets for halting the progression of pulmonary fibrosis in patients with IPF. Care should be taken when managing patients with IPF with anesthetics given evidence of their impact on HIF1A stabilization (42)(43)(44)(45). Future work will include elucidating the impact of hypoxia-independent pathways, whether stretch induced or metabolite mediated, on upstream HIF1A stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the substitution between the two isoenzymes is remarkable, and, in fact, the protein levels of L-PFK2 almost disappear and are substituted by the uPFK2 form in the course of TLR-2, -3, -4, or -9 activation, despite the use of nonredundant signaling pathways (i.e., MyD88-dependent and independent pathways). One likely mechanism to explain this switch between PFK2 isoenzymes after classic activation is the rise in the levels of Hif-1a because a functional relationship has been described between the hypoxia-responsive element motifs present in the uPFK2 promoter and the expression of this isoenzyme (16,18,19,22,23,53). Accordingly, experiments in macrophages lacking Hif-1a were carried out with the idea to impair uPFK2 expression.…”
Section: Discussionmentioning
confidence: 99%